The Effect Of Using The Writing Processes Approach On Improving The Essay Writing Skill Of Undergraduate Students/ أثر استخدام مدخل عمليات الكتابة في تحسين مهارة كتابة المقالة لدى طلاب المرحلة الجامعية - Tarig Muhmmad Almugim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Writing is a necessary skill in the primary and university education stages. To master this skill, the teacher must search for strategies to help him improve the level of his students. Among these strategies is the entrance to improving writing, which are psychological and skillful processes the writer goes through before, during, and after writing. The researcher chose them to teach the essay to undergraduate students, which are five stages. The researcher added additional strategies for the first stage in the entrance to the processes related to what precedes the writing stage. Where he said psychological preparation so that the student is convinced of the importance of reading and its connection to writing, and training in reading and summarizing so that the student can retrieve his acquired language skills, then the theoretical introduction so that he gets to know the features of the article and its most prominent writers and models from it, and the researcher applied the rest of the strategies as it came to the previous students, and the results of that method were It is satisfactory, as the students' performance improved compared to the traditional methods that did not take into account the gradual acquisition of the skill, and the accompanying psychological stages.